Characterization of Algae Dietary Supplements Using Antioxidative Potential, Elemental Composition, and Stable Isotopes Approach - Kejžar, Jan; Jagodic Hudobivnik, Marta; Nečemer, Marijan; Ogrinc, Nives; Masten Rutar, Jasmina; Poklar Ulrih, Nataša (Frontiers in Nutrition, 2021)
Dietary supplements based on algae, known for their nutritional value and bioactive properties, are popular products among consumers today. While commercial algal products are regarded safe by numerous studies, information about the production and origin of such products is scarce. In addition, dietary supplements are not as strictly regulated as food and medicinal drugs. We characterized different algal products (kelp - Laminariales, Spirulina spp., Chlorella spp. and Aphanizomenon flos-aquae), obtained on Slovenian market, based on their elemental composition (XRF, ICP-MS), antioxidative potential (DPPH assay, total phenolic content) and stable isotope values (C, N and S; EA-IRMS method). Antioxidative potential is consistent among products of the same type, with A. flos-aquae samples having 4.4 times higher antioxidative potential compared to Chlorella spp. and 2.7 times higher compared to Spirulina spp. Levels of toxic trace elements (As, Cd, Hg and Pb) are below the maximum allowed values and as such do not pose risk to consumers’ health. Samples of Spirulina spp. have relatively high δ15N (7.4 ± 4.4 ‰) values, which indicate use of organic nitrogen sources in certain samples. Likewise, different elemental composition and isotopic ratios of stable elements (C, N and S) for the samples with Spirulina spp. or Chlorella spp. are the consequence of using different nutrient sources and algae growing techniques. Statistical analysis (principal component analysis) has confirmed that all tested A. flos-aquae samples originate from the same source, supposedly lake Klamath (Oregon, USA). Hawaiian S. pacifica can also be differentiated from all the other samples due to its characteristically high metal content (Fe, Mn, Zn, Co, Ni, V). Chlorella spp. and Spirulina spp. require further analyses with larger number of samples, as differentiation is not possible based on results of this study.